Torrefação do bagaço de cana-de-açucar para fins energéticos - Melles, Victor [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Bagasse and straw are residues from the industrial processing of sugarcane that constitute an important source for cogeneration of energy in the sugar-alcohol sector, but the bagasse presents properties as a high moisture content, low density and low energy density, resulting in a low energy efficiency of the biomass and loss of materials due to deterioration. One of the alternatives for improving these properties is the application of the torrefaction process, which consists of a thermal pretreatment of biomass in that the raw biomass is heated in an inert atmosphere at temperatures of 200 to 300 ° C. The torrefaction process allows the conversion of raw biomass into solid fuel suitable for combustion and gasification. Torrified biomass has better properties, such as higher energy density, lower hydrophilic nature, lower ratio of O / C and H / C atoms, and greater ease of storage and transport. In this work, it is proposed to conduct thermal studies to evaluate the applicability of the torrefaction process in the residual sugarcane bagasse in a sugar-alcohol industry. The experiments were run at 200 and 300 °C for 30 and 60 minutes. In order to verify the effect of the roasting process on the thermal characteristics of the bagasse, the results of the higher heating value (HHV) were analyzed, which allow to evaluate the energetic gain in the torrified bagasse, and the results of the thermogravimetric tests that determine the conversion rates and the reaction rate coefficients. The torrified BCA showed an increase in HHV, reduction of moisture content and reduction of material volume in all cases

O bagaço é um resíduo do processamento industrial da cana-de-açúcar que constitui uma importante fonte de recurso para cogeração de energia no setor sucroalcooleiro, porém o bagaço apresenta propriedades como um alto teor de umidade e baixa densidade energética, resultando em uma baixa eficiência energética da biomassa e perdas por deterioração. Uma das alternativas para melhorar estas propriedades é a aplicação do processo de torrefação, que consiste em um pré-tratamento térmico de biomassa em que a biomassa in natura é aquecida em uma atmosfera inerte a temperaturas de 200 a 300 ° C. O processo de torrefação permite a conversão de biomassa in natura em combustível sólido adequado para combustão e gaseificação. A biomassa torrificada tem melhores propriedades, tais como maior densidade de energia, menor natureza higroscópica, menor relação de átomos de O/C e H/C e maior facilidade para armazenamento e transporte. Neste trabalho, propoe-se realizar estudos térmicos para avaliar a aplicabilidade do processo de torrefação no bagaço de cana-de-açúcar residual em uma indústria sucroalcooleira. Os experimentos foram realizados a 200 e 300 °C durante 30 e 60 minutos. Para verificar o efeito do processo de torrefação nas características térmicas do bagaço foi determinado a análise imediata e o poder calorífico superior (PCS), que permitem avaliar o ganho energético no bagaço torrificado, e os resultados dos ensaios de termogravimetria que determinam as taxas de reação, conversão e os coeficientes de taxa de reação. O BCA torrificado apresentou um aumento no PCS, redução do teor de umidade e redução de volume de material em todos o casos
Keywords: Bagaço de cana; Pirolise; Analise termica; Energia - Fontes alternativas; Bagasse